PENGARUH PENDAPATAN DESA DAN ALOKASI DANA DESA TERHADAP BELANJA DESA DAN KEMISKINAN - Ratna Sari Dewi; Ova Novi Irama (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2018)
The study aims to analyze direct and indirect effects of village income and village fund allocation on spending of village expenditure budget and poverty. The respondents of the study which was a sample of population, was 81 governments of village in North Sumatra Province. The data gained from 2014 to 2016 was processed and the purposive sampling method was used to determine the number of samples with certain criteria based on the APBDes report and the poverty level report of the district government of North Sumatra Province. Data were analyzed based on multiple linear regression processes with f test and t test for hypothesis verification. The results of the study showed that village income and village fund allocation have a direct influence on village expenditure budget and poverty.